PENGARUH TRANSFORMASI PERAN PEREMPUAN DAN SENSITIVITAS GENDER TERHADAP PERILAKU MEMILIH BURUH PEREMPUAN PLASMA PADA PEMILIHAN KEPALA DAERAH PURBALINGGA 2020 - Alberto Noviano Patty; Rina Martini; Nur Hidayat (Institut Pendidikan Tapanuli Selatan, 2022)
This article to provide an understanding for every reader provide effective understanding The Influence of Transforming the Role of Women and Gender Sensitivity on the Voting Behavior of Plasma Female Workers at Purbalingga Regional Head Election 2020. To approach this problem, the theoretical reference from John Rawls (2019:657) Theory of justice, rationally of votting behavior will come from a moral person want to equality, meaning a person who has a conception of a rational life plan who wants justice. The data were collected through the explanatory survey research method, use of questionnaire primary data based on the answers of 100 respondents, method analyzed quantitatively, using statistical package for the social science (SPSS). This study concluded, accepting the first hypothesis, there was a positive influence of Y= 1.700+0.037 variables female role transformation on voting behavior, with an influence of 86.4%. Accepting the second hypothesis, there was a positive influence of Y= 6.898+0.142 variables gender sensitivity to voting behavior, with an influence of 50.5%. Accepting the third hypothesis, there was an influence of 89.9% simultaneously, on the variables of female role transformation and gender sensitivity variables, on the voting behavior of plasma female workers, Purbalingga regional head election 2020.